Profesionalisme Guru Menghadapi Masyarakat Ekonomi ASEAN - Mikael Nardi (Cokroaminoto Journal of Primary Education, 2018)
Nowadays, teacher professionalism is a fundamental issue in education sector due to the following reasons. Firstly, the data of UKG results in 2015 indicates that the teachers are not competent. Secondly, the global situation requires teachers to produce competent, independent, and competitive human resources. Facing the era of Asean Economic Community (MEA), teachers are increasingly required to be more competent in order to produce qualified and competitive Indonesian human beings. In order to improve the teacher professionalism, there are two key ideas that are important to do. First, Continuing Professionalism Development (CPD), ie a natural learning experience and deliberate activities planned to provide direct benefits to teachers and the quality of learning in the classroom. Second, ongoing formation, ie activities that are voluntarily performed by teachers without coercion from other parties. For example, the teachers take special time to study by reading books, taking courses, workshops or seminars. These are possible if the teachers have the will to be better.